PENGARUH POLA ASUH ORANG TUA TERHADAP DISIPLIN BELAJAR SISWA SEKOLAH DASAR NEGERI SUKAHATI 01 - Sri Puji Rahayu; Tatang Muhajang (Universitas Pakuan, 2021)
THE INFLUENCE OF PARENTING PATTERNS ON STUDENT LEARNING DISCIPLINEThe parent’s upbringing of the student discipline. Primary School Teacher Education Study Program. The Faculty of Teacher Training and Educational Sciences Pakuan University Bogor 2021. This research is a quantitative research with a causal approach. The study is aimed at recognizing the effect a parent’s upbringing has on the discipline of students of fourth grade students in SDN Sukahati 01 Citeurep District, Bogor Regency. The population of this study was 90 students with a total sample of 47 students. Studies indicate that the effect of a parent’s upbringing on a student’s learning discipline is indicated by a statistical analysis that results in coeffiencies in correlation (rxy) of 0,53. The indicates the effects of a parent’s upbringing on students learning discipline, while coefficiencies of determination(r2) of 0,28 or 28%. The reamaining 72% determined by other factors.The average the students learning discipline of students by 28% determined by a parent’s upbringing through regression equations Ŷ= 74,26 + 0,41X, thus means that each increase in the unit value of parenting will cause an increase in student learning discipline by 0,41 units. Based on the results of this study, there can be a positive influence between a parent’s upbringing and student discipline the fourth grade students in SDN Sukahati 01 Citeurep District, Bogor Regency, odd semester of the 2020/2021.